Studying Signs of Diastolic Dysfunction of the Right Ventricle in Patients with Hypertonic Disease (Global Journal of Medical Research, 2020)
Hypertension is currently one of the most pressing medical problems. This is largely due to the fact that arterial hypertension, which is largely responsible for high cardiovascular morbidity, disability and mortality, and is also characterized by a wide prevalence. Early diagnosis of changes in the heart in patients with essential hypertension is of great practical interest, which allows timely preventive measures and treatment. As a rule, with arterial hypertension, the left ventricle is primarily and to a greater extent affected, since the main load falls on it from the very beginning of the disease. The analysis of parameters of diastolic function of the right ventricle was carried out depending on the level of rise in diastolic blood pressure between patients with mild and high arterial hypertension. At the same time, significant differences were revealed that related to the ratio of the maximum filling rate to the maximum expulsion rate.
Keywords: essential hypertension; arterial hypertension; diastolic dysfunction; right ventricle